2020
DOI: 10.1088/1742-6596/1542/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality Controllers and Comparison Between Vive, Leap Motion and Senso Gloves Applied in The Anatomy Learning System

Abstract: The availability of control devices that use hand and finger movements in virtual reality systems has an essential role in increasing the level of interaction in the virtual reality system. Hand and finger movements in a virtual reality system can be displayed either in the form of a controller that resembles its original shape or in the form of a virtual hand. The translation motion and rotation of the virtual reality controller can be used as input to the system. In addition, the virtual reality controllers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…After asking for qualitative feedback, we discovered that users' expectations were better confirmed while using hand gesture recognition, as shown in Table 10. This finding supports Kharoub et al's [47] claim that consumers have expectations for gesture recognition. In contrast, the joystick controller shows a limitation for the virtual experience, After asking for qualitative feedback, we discovered that users' expectations were better confirmed while using hand gesture recognition, as shown in Table 10.…”
Section: Satisfaction and Confirmationsupporting
confidence: 88%
See 1 more Smart Citation
“…After asking for qualitative feedback, we discovered that users' expectations were better confirmed while using hand gesture recognition, as shown in Table 10. This finding supports Kharoub et al's [47] claim that consumers have expectations for gesture recognition. In contrast, the joystick controller shows a limitation for the virtual experience, After asking for qualitative feedback, we discovered that users' expectations were better confirmed while using hand gesture recognition, as shown in Table 10.…”
Section: Satisfaction and Confirmationsupporting
confidence: 88%
“…Users only need to know where the buttons are to operate the system (see Table 8). This verifies the fact that the joystick controller is not difficult for users to learn, as suggested by Tanjung et al [47]. For the use of hand gesture recognition, this study observed that some users, whose hand gestures were standard, completed the tasks efficiently (in 15 min), and these users believed that the hand gesture recognition was not challenging for them to learn.…”
Section: Perception Of Internal Controlsupporting
confidence: 84%
“…Vibrotactile stimulation is both low-cost, low-power, and low-profile, allowing for it to be attached in a variety of locations within the hand. Many electronic devices including phones and computers make use of vibrations for alerts and most commercially available virtual reality systems such as the Oculus Quest and HTC Vive make use of vibrotactile stimulation as their primary form of cutaneous feedback [120]. Vibrotactile phantom stimulation is used to provide the illusion of slippage and weight onto objects by way of a series of magnetic pins that vibrate in response to interactions in the virtual system [121,122].…”
Section: Vibrotactile Stimulationmentioning
confidence: 99%
“…Tasks involving grasping or pointing are examples of movements that can be used to initiate interaction between the operator and the environment. 64 Controllers such as the leap motion controller 25 and quest controller 46 are widely used in the chemical safety domain. These controllers are generally equipped with haptic feedback, i.e., touch experience by applying forces, vibrations, or motions to the user.…”
Section: Guidelines For Development Andmentioning
confidence: 99%
“…Such controllers become very relevant for operator training as they require moving around and interacting with process equipment (manipulating valves). Tasks involving grasping or pointing are examples of movements that can be used to initiate interaction between the operator and the environment . Controllers such as the leap motion controller and quest controller are widely used in the chemical safety domain.…”
Section: Guidelines For Development and Deployment Of Vrmentioning
confidence: 99%